FAKTOR-FAKTOR YANG MEMENGARUHI PRODUKSI USAHATANI BAWANG MERAH LEMBAH PALU DI DESA LABUAN TOPOSO KECAMATAN LABUAN KABUPATEN DONGGALA - Moh Sigit Maradhika; Max Nur Alam; Effendy Effendy (Universitas Tadulako, 2022)
The production of Palu valley shallots in Labuan Toposo Village is 302 tonnes with a harvest area of 76 ha, where Labuan Toposo Village is the village that has the highest production of Palu valley shallots (302 tonnes for 76 ha or 3.9 tonnes / ha). This research aims to determine the effect of production factors on land area, seeds, urea fertilizer, ZA fertilizer, Ponska fertilizer and labor on Palu valley shallot production in Labuan Toposo Village, Labuan District, Donggala Regency.The data analysis used is the Cobb-Douglas production analysis.Based on the results of the analysis and discussion of the data above, conclusions can be drawn by looking at the value of Fcount 30.976 ˃ F table 2.49 at α = 5%, which means that the null hypothesis (H0) is rejected, so the independent variables are land area, seeds, urea fertilizer, ZA fertilizer, Ponska fertilizer and labor (simultaneously) have a significant effect on Palu valley shallot production in Labuan Toposo Village. Whereas partially or respectively the influence of the Urea fertilizer, ZA fertilizer, Ponska fertilizer, and Labor variables had no significant effect on production, while the use of land area and seed variables had a significant effect on Palu valley shallot production in Labuan Toposo Village, Labuan District. Donggala Regency